Development of magnetic, ferrite supported palladium catalysts for 2, 4-dinitrotoluene hydrogenation. (June 2021) - Hajdu, V.; Varga, M.; Muránszky, G.; Karacs, G.; Kristály, F.; Fiser, B.; Viskolcz, B.; Vanyorek, L.
Abstract: Cobalt, copper, and nickel ferrite spinel nanoparticles have been synthesized by using a combination of sonochemical treatment and combustion. The magnetic nanoparticles have been used as supports to prepare 4 wt% palladium catalysts. The ferrites were dispersed in an ethanolic solution of Pd(II) nitrate by ultrasonication. The palladium ions were reduced to metallic Pd nanoparticles, which were then attached to the surface of the different metal oxide supports. Thus, three different catalysts (Pd/CoFe2 O4, Pd/CuFe2 O4, Pd/NiFe2 O4 ) were made and tested in the hydrogenation of 2, 4-dinitrotoluene (DNT). A possible reaction mechanism, including the detected species, has been envisaged based on the results. The highest 2, 4-diaminotoluene (TDA) yield (99 n/n%) has been achieved by using the Pd/NiFe2 O4 catalyst. Furthermore, the TDA yield was also reasonable (84.2 n/n%) when the Pd/CoFe2 O4 catalyst was used. In this case, complete and easy recovery of the catalyst from the reaction medium is ensured, as the ferrite support is fully magnetic. Thus, the catalyst is very well suited for applicationy in the hydrogenation of DNT or other aromatic nitro compounds. Highlights: Application of cobalt, copper, and nickel ferrite catalyst supports. Simplified and fast catalyst preparation method. Magnetic separable ferrite supported palladium catalysts. High catalytic activity in hydrogenation of TDA.